EVALUASI PROGRAM GERAKAN NASIONAL CINTA MUSEUM (GNCM) PADA MUSEUM BALI - Sakti, Zipora Lorentina; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 3 No 1 (2015): VOL 3, NO 1 (2015): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2015.v03.i01.p09, 2015)
ABSTRACT In effort to put the museum on the fact that the strategic position, the necessary movements with strengthening the understanding, appreciation, and concern for the development of national culture and identity. Joint movement is called the National Movement of Love Museum (GNCM). To determine the extent to which the program can be run, it is necessary to evaluate the program. It aims to determine the implementation of the program of the National Movement Love Museum (GNCM), especially in a museum revitalization activities in the Museum of Bali, so that academic and practical benefits can also be achieved. This study uses data collection techniques with observation, interviews, and library research. Type of data used is quantitative and qualitative data, obtained from the data sources, both primary and secondary. To obtain information determination techniques used by purposive sampling and data analysis technique used is descriptive qualitative use of Evaluation Theory Tree (tree evaluation theory). Based on the results of the study, explained that the program Love Museum National Movement (GNCM), especially in the museum revitalization activities conducted at Bali Museum, can run well, it's just that there are some drawbacks. Advice can be given, among others, between the parties related to Love Museums program of the National Movement (GNCM) should always give priority to the coordination and good cooperation.
Keywords: Evaluation, Program National Movement of Love Museum (GNCM), Revitalization.